Penegakan Hukum Terhadap Pelaku Penyebaran Konten Asusila - Salmon, Harly Clifford J; Latumaerissa, Denny; Saimima, Judy Marria (Jurnal Risalah Hukum, 2025)
The purpose of this study is to examine and analyze law enforcement against asusila content spreaders as well as to examine and meganalyze obstacles in law enforcement against asusila content spreaders.This study uses empirical juristic research methods.The jurisdictions approach is used to analyze the legislative regulations relating to the dissemination of the content of the asusila.Empirical approaches are used to analyze empirical data obtained from the study of documents and interviews with key informants.As for the results of this study, which is enforcement against perpetrators of the spread of content asusila involves several steps starting from the investigation, Investigation, until the trial.This process involves various institutions, including police, The prosecution, and the court.Somerules that are the legal basis that can be applied to the perpetrators of the distribution of pornographic content among others: kuhp, The National Institute of Allergy and Infectious Diseases . pornography law, the obstacles in law enforcement the  content porno is the lack of data to restore the availability of video or photographs that contain a pornography, when unexpected perpetrators have remove the data, so as to the evidence and investigators must bring attendant / investigators suspected cell phone video as well as a photograph in which is intended to labs digital forensic police in makassar, and not a ite in maluku, to ask the expert testimony and evidence to support should come from outside the maluku ite notabenenya memelukan large enough money.